Salivary biomarkers of oxidative stress in children with dental caries: Systematic review and meta-analysis - Martins, Jordana Resende [UNESP]; Díaz-Fabregat, Beatriz [UNESP]; Ramírez-Carmona, Wilmer [UNESP]; Monteiro, Douglas Roberto [UNESP]; Pessan, Juliano Pelim [UNESP]; Antoniali, Cristina [UNESP] (Elsevier, 2022)
Objective: To assess the relationship between salivary biomarkers of oxidative stress and dental caries in children. Methods: Studies conducted in children up to 12 years old comparing salivary biomarkers of oxidative stress such as malondialdehyde (MDA), superoxide dismutase (SOD), uric acid, and total antioxidant capacity (TAC), considering children with dental caries lesions and caries-free ones were selected. In addition, salivary parameters such as salivary flow, pH, buffering capacity, calcium and total protein levels were evaluated. A systematic literature review was carried out in 8 databases. The standardized mean difference (SMD) was measured using inverse variance as a statistical method and random effects as an analysis model, corresponding to a 95% confidence interval (CI). Results: The TAC levels were higher in children affected by dental caries compared to caries-free ones (control group), regardless of age (SMD 2.66, CI 1.33, 3.98), or gender (SMD 0.98, CI 0.56, 1.39). When adjusted for normalized protein, MDA levels were lower in the dental caries group than in the control group (SMD −16.51, CI −29.02, −4.00), and SOD levels were higher in the dental caries group (SMD 5.09, CI 0.01.10.18). The total protein concentration in saliva of children with dental caries was higher than in the control group, regardless of age (SMD 0.98, CI 0.27, 1.69), or gender (SMD 0.77, CI 0.45, 1.10). The salivary parameters assessed had lower levels in children affected by dental caries (p < 0.05). Conclusions: The levels of oxidative stress biomarkers and salivary parameters are altered in saliva of children with dental caries.
Keywords: Biomarker; Dental caries; Oxidative damage; Saliva; Salivary proteins and peptides